2019
DOI: 10.1177/2473974x19875077
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Experience of Treatment and Outcomes for Cutaneous Periauricular Squamous Cell Carcinoma

Abstract: ObjectivesTo report our institutional experience, management, and outcomes of cutaneous periauricular squamous cell carcinoma (SCC).Study DesignRetrospective chart review.SettingTertiary academic center.SubjectsPatients undergoing treatment of cutaneous periauricular SCC from 2000 to 2016.ResultsA total of 112 patients had a median follow-up of 24.5 months, a mean ± SD age of 75.7 ± 10.6 years, and a strong male predominance (93.8%). Site distribution shows 87 (77.7%) auricular, 26 (23.2%) preauricular, and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 26 publications
3
21
0
1
Order By: Relevance
“…18 However, limited reports stratify the lesions to specific anatomic subsites. 19 Of all periauricular/auricular lesions, we found that most tumors arise primarily on the auricle (80.3%), though the true primary site location may be a blend of periauricular locations if we consider prior management of pre- and postauricular lesions by services other than otolaryngology or lesions managed with MMS. Within the auricle, most BCC occurred in the conchal bowl, followed by the helix, while very few cases (2.8%) were located in the EAC proper, consistent with typical anatomic regions with greater exposure to UV light.…”
Section: Discussionmentioning
confidence: 79%
“…18 However, limited reports stratify the lesions to specific anatomic subsites. 19 Of all periauricular/auricular lesions, we found that most tumors arise primarily on the auricle (80.3%), though the true primary site location may be a blend of periauricular locations if we consider prior management of pre- and postauricular lesions by services other than otolaryngology or lesions managed with MMS. Within the auricle, most BCC occurred in the conchal bowl, followed by the helix, while very few cases (2.8%) were located in the EAC proper, consistent with typical anatomic regions with greater exposure to UV light.…”
Section: Discussionmentioning
confidence: 79%
“…The majority of cSCC tumors arise in the sun-exposed H&N region. 6,14,15 Successful treatment of primary cSCC-HN tumors can be complicated and extensive due to adjacent and underlying critical structures (e.g., skull base, eyes, facial nerve [CN VII], spinal accessory nerve, auditory canal, parotid gland). 14,32 High-risk tumors can have aggressive behavior with increased likelihood for metastasis and/or local recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical locations of the primary cSCC-HN tumor were categorized similarly to previous reports describing common sites of cSCC in the H&N region. 5,14,[25][26][27][28] Following comprehensive review of pathology reports and medical records, each case was completely staged via AJCC8 and BWH tumor staging systems [19][20][21] and categorized as very high, high, or low risk per current NCCN guideline definitions. 5 Characteristics and 40-GEP test results were analyzed for the cohort to determine significant differences between metastatic and nonmetastatic cases as previously described.…”
Section: Cohort Demographics Clinical Characteristics and Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 These high‐risk factors are often associated with more aggressive cancer growth, which can lead to recurrence, metastasis, and disease‐specific death (DSD). 1 , 8 Tumors located in the head and neck area account for more than 50% of new cSCC lesions, 9 , 10 are considered high risk by the National Comprehensive Cancer Network (NCCN) if located in the mask area of the face at any size or if located in other areas of the head and neck at ≥1 cm, 7 and pose unique challenges for surgical resection and treatment. The NCCN guidelines; as well as the American Joint Committee on Cancer (AJCC) Cancer Staging Manual, Eighth Edition (AJCC8); Union for International Cancer Control (UICC), Eighth Edition; and Brigham and Women's Hospital (BWH) staging systems, use clinicopathologic features of the primary tumor to categorize risk of poor outcomes in cSCC.…”
Section: Introductionmentioning
confidence: 99%